Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Pada Logam Mulia ANTAM di Jakarta Selatan - Dhea Aprillia; Purwatiningsih Purwatiningsih (Pusat Riset dan Inovasi Nasional, 2026)
Gold prices tend to fluctuate over time, which may influence consumers' decisions when purchasing precious metals. In addition, the wide variety of gold investment products available in the market has made consumers more selective in choosing the products they intend to purchase. Under these circumstances, price and brand image are considered factors that may affect consumers' purchasing decisions toward ANTAM gold bullion products. This study aims to examine the influence of price and brand image on purchasing decisions of ANTAM gold bullion in South Jakarta. This research employed a quantitative method, with data collected through questionnaires distributed to 96 respondents who had previously purchased ANTAM gold bullion. The sampling technique used was purposive sampling. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that price has a positive and significant effect on purchasing decisions, with a t-value of 4.592 and a significance value of 0.001. Brand image also has a positive and significant effect on purchasing decisions, with a t-value of 4.604 and a significance value of 0.001. Simultaneously, price and brand image significantly influence purchasing decisions, as indicated by an F-value of 80.826 and a significance value of 0.001. The coefficient of determination of 63.5% indicates that price and brand image are able to explain 63.5% of the variation in consumers' purchasing decisions.